Kajian Strategi Pengembangan Potensi Desa Wisata Paralayang Gunung Bungkuk Di Kabupaten Magetan - Dhikriana, Mifta Rina; HAKIM, RAHMAN; Suwarno, Suwarno; Alfarizi, Tito; Setyawan, Katon Galih (Journal of Applied Community Engagement, 2024)
This research is a feasibility study for the development of a paragliding tourism village in Gunung Bungkuk, Magetan, with the primary objective of determining the strategic development plan for paragliding destinations in the area. This study utilizes the SWOT method for identification and formulation of strategic plans, alongside the guidelines provided by the Ministry of Tourism and Creative Economy for pilot tourism villages. The results of this research can serve as the basis for decisions regarding the continuation of the development of the paragliding tourism village, including the formulation of management strategies, risk mitigation efforts, and enhancement of economic, social, and environmental potential in the area. Therefore, this research is expected to make a significant contribution to sustainable tourism development in the region.